Acrylamide in industrial potato crisp manufacturing: A potential tool for its reduction. (April 2020) - Ledbetter, Moira; Bartlett, Leanne; Fiore, Alberto; Montague, Gary; Sturrock, Keith; McNamara, Ged
Abstract: This paper considers the potential for identifying industrial manufacturing conditions that will lead to high acrylamide formation in potato crisp manufacture. Considering the available historical industrial processing data, initial tests were undertaken to identify the degree of variability and confidence in the data. Following data visualisation which indicated data 'fingerprints' characteristic of high acrylamide, Partial Least Squares (PLS) Discriminant Analysis (DA) was implemented to provide indications of the probability that high acrylamide product would be produced. It was determined that in a third of instances, high acrylamide could be predicted while maintaining a low level of false predictions. The predominance of fructose concentration in the prediction along with the need for asparagine were indicated and aligned well with prior literature mechanistic model indications. The ability to identify a third of high acrylamide occurrences provides the process operators with a good opportunity to make process modifications that would comply with increasingly stringent regulation. Highlights: PLS on potato precursors has been applied to predict acrylamide formation within a factory setting. The same approach to develop a prediction tool could be applied to other factories. Approach allows food sector to monitor raw material suitability prior to processing.